2018
DOI: 10.5455/aim.2018.26.87-92
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of IL-10 Gene and Protein in Target Tissues of Rattus Norvegicus Strain Wistar Model Type 2 Diabetes Mellitus (T2DM)

Abstract: Introduction:Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease caused by insulin resistance. Insulin resistance leads to hyperglycaemia that causes complication such as microangiopathy and macroangiopathy. The immune system of T2DM will be produce IL-10 as an anti-inflammatory cytokine role immune-stimulator and immunosuppressant in the organ system. This present study investigated of IL-10 gene profile and protein expression in the rat organ (Rattus norvegicus) strain Wistar model T2DM.Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
10
0
4
Order By: Relevance
“…When inflammation occurs, the body will respond by forming anti-inflammatory cytokines to produce symptoms of inflammation. Bare et al, (2018) in the previous study reported the protein profile of all tissues in inflammation (type 2 diabetes mellitus) group and the normal group was completely diverse as proper by Experion Pro260 analysis besides in SDS-PAGE analysis show same results.…”
Section: Introductionmentioning
confidence: 68%
“…When inflammation occurs, the body will respond by forming anti-inflammatory cytokines to produce symptoms of inflammation. Bare et al, (2018) in the previous study reported the protein profile of all tissues in inflammation (type 2 diabetes mellitus) group and the normal group was completely diverse as proper by Experion Pro260 analysis besides in SDS-PAGE analysis show same results.…”
Section: Introductionmentioning
confidence: 68%
“…Hypertension is one of factor to Type 2 Diabetes Mellitus. In Case of high glucose showed has different profile protein compare with normal conditions (case of Type 2 Diabetes Mellitus) Bare, Marhendra, Sasase, & Fatchiyah, 2018).…”
Section: E E L L --H H a A Y Y A A H H 1 Introductionmentioning
confidence: 93%
“…Sistem imun merespon dengan melepaskan mediator sitokin antiinflamasi seperti IL-10 untuk menekan inflamasi yang yang terjadi di dalam tubuh. Akan tetapi penelitian Bare, Marhendra, Sasase, & Fatchiyah, (2018) melaporkan pada saat inflamasi gen IL-10 mengalami mutasi pada organ lambung dan otak. Mutasi yang terjadi menyebabkan menurunkan kinerja IL-10 sebagai anti-inflamasi.…”
Section: Pendahuluanunclassified